2018
DOI: 10.1016/j.ijrobp.2018.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Dose-limiting Urinary Toxicity With Pembrolizumab Combined With Weekly Hypofractionated Radiation Therapy in Bladder Cancer

Abstract: There is currently significant interest in the potential benefits of combining radiation and immune checkpoint blockade (ICB) to stimulate both regional and distant abscopal immune responses. In melanoma and lung cancer, patients who have received radiation therapy during ICB appear to have prolonged survival. The PLUMMB trial (Pembrolizumab in Muscle-invasive/Metastatic Bladder cancer) (NCT02560636) is a phase I study to test the tolerability of a combination of weekly radiation therapy with pembrolizumab in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 8 publications
0
55
0
1
Order By: Relevance
“…In fact, in patients with bladder cancer, dose‐limiting urinary toxicity was reported when anti‐PD‐L1 antibodies were combined with radiotherapy. [ 69 ]…”
Section: Radiotherapy and Its Immunomodulatory Effectmentioning
confidence: 99%
“…In fact, in patients with bladder cancer, dose‐limiting urinary toxicity was reported when anti‐PD‐L1 antibodies were combined with radiotherapy. [ 69 ]…”
Section: Radiotherapy and Its Immunomodulatory Effectmentioning
confidence: 99%
“…One explanation for LC improvement with hypofractionated WBRT is UC radioresistance responding favorably to higher RT doses per fraction [90]. Several trials demonstrated improved LC with hypofractionated RT for unresectable BC; however, combining hypofractionated RT with ICB may exacerbate treatment toxicity [91][92][93]. In the absence of larger, more robust data showing a consistent benefit for hypofractionated WBRT, we favor 30 Gy/10 fraction WBRT for multiple unresectable lesions, with consideration of hippocampal avoidance WBRT and concurrent and adjuvant memantine for eligible patients.…”
Section: Whole Brain Radiation Therapy and Best Supportive Carementioning
confidence: 99%
“…There is a 5% incidence rate of pneumonitis in conjunction with PD-1/PD-L1 blockade (17), and this approximately doubles when given in combination with CTLA-4 inhibition (18). Toxicity profiles of immune checkpoint inhibitors also vary as a function of combination with chemotherapies (19) and ionizing radiation (20,21). For example, a phase I study to test the tolerability of pembrolizumab and radiation therapy in patients with metastatic or locally advanced urothelial cancer of the bladder was paused due to grade 3 bladder toxicities although the radiation dosing schedule is normally well-tolerated alone.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a phase I study to test the tolerability of pembrolizumab and radiation therapy in patients with metastatic or locally advanced urothelial cancer of the bladder was paused due to grade 3 bladder toxicities although the radiation dosing schedule is normally well-tolerated alone. The investigators plan to mitigate these in field toxicities by de-escalating the radiation dose (20).…”
Section: Introductionmentioning
confidence: 99%